Perbandingan labilitas emosi anak usia 5-6 tahun dari ibu pekerja dan ibu rumah tangga di Banjarmasin - Haida, Rizki Noor; Aisya, Rihdatul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2026)
This study aims to compare the level of children's emotional lability between working mothers and stay-at-home mothers in Banjarmasin. Using a quantitative approach with a causal-comparative design, this study involved 114 mothers of early childhood (PAUD/TK) selected through simple random sampling. The research instrument was a psychological scale adapted from the Lability/Negativity aspect of the Emotion Regulation Checklist (ERC). The results of the hypothesis test using the Independent Sample t-Test showed a significance value of 0.003 (p < 0.05), indicating a significant difference in the level of children's emotional lability between the two groups. The findings revealed that children of stay-at-home mothers had a higher average emotional lability score than children of working mothers. This indicates that the quality of interaction and the psychological well-being of the mother are more determinant in maintaining the child's affective stability than mere physical presence at home.